Frontofacial Surgery: Reducing Infection with the Development and 6-Year Outcome of a Frontofacial Protocol - White, Andrea; van de Lande, Lara S; O'Hara, Justine; Hartley, John; Hayward, Richard; James, Greg; Jeelani, N Owase; Dunaway, David J (Plastic and reconstructive surgery (1963), 2023)
Frontofacial surgery (FFS) creates a communication between the cranial and nasal cavities and is associated with significant infection risk. After a cluster of infections affecting patients undergoing FFS, a root cause analysis of index cases was undertaken, but no specifically remedial causes were identified. Basic principles incorporating known risk factors for the prevention of surgical-site infection were then applied to the creation of a perioperative management protocol. This study analyzes infection rates before and after its implementation. The protocol was designed around the needs of patients undergoing FFS and consists of three checklists covering their preoperative, intraoperative, and postoperative care. Compliance required the completion of each checklist. All patients undergoing FFS between 1999 and 2019 were studied retrospectively, and infections occurring before and after the implementation of the protocol were analyzed. One hundred three patients underwent FFS (60 monobloc and 36 facial bipartition) before the implementation of the protocol in August of 2013, and 30 patients underwent FFS after its implementation. Compliance with the protocol was 95%. After implementation, there was a statistically significant reduction in infections from 41.7% to 13.3% ( P = 0.005). Although no specific cause for a cluster of postoperative infection had been identified, the implementation of a bespoke protocol consisting of preoperative, perioperative, and postoperative checklists covering measures known to reduce infection risk was associated with a significant reduction in postoperative infections in patients undergoing FFS. Therapeutic, III.